Antidiabetic Potential of Combined Extracts of Ageratum Conyzoides and Cyperus Rotundus: in Vivo Study - Wahyu Rahmatulloh; Laeli Fitriyati; Tri Cahyani Widiastuti; Dwiana Rahmi Nur Rofiqoh; Aryadi Suryanata Kusuma; Muh Fathurrahman (Indonesian Journal of Global Health Research, 2026)
Long-term use of synthetic antidiabetic drugs often causes side effects, prompting the search for safer herbal alternatives. Ageratum conyzoides and Cyperus rotundus are known for their antihyperglycemic properties, but studies on their combination remain limited. To evaluate the antihyperglycemic effect of combined ethanol extracts of A. conyzoides leaves and C. rotundus rhizomes in streptozotocin (STZ)-induced diabetic rats. Male white rats were divided into nine groups: control, single extract, and combination treatments (100:200 and 150:500 mg/kg BW). Treatments were given orally for 15 days, and blood glucose levels were measured periodically. Data were analyzed using one-way ANOVA and Tukey's post hoc test. The combination of A. conyzoides and C. rotundus (150:500 mg/kg BW) significantly reduced blood glucose levels, comparable to glimepiride (p < 0.05 vs. negative control; p > 0.05 vs. positive control). Single extracts showed moderate effects in a dose-dependent manner. The combination of A. conyzoides and C. rotundus extracts exhibited synergistic antihyperglycemic activity, suggesting potential as a safe phytotherapeutic alternative for diabetes management.